Weaponization of Wokeness: The Theater of Management and Implications for Public Administration. (22nd March 2022) - Zavattaro, Staci M.; Bearfield, Domonic
Abstract: Contemporarily, the word "woke" has moved into the popular lexicon, largely to mean aware of and ideally doing something about systemic racism. After the George Floyd murder, and many other state‐sanctioned murders of Black Americans, protests erupted globally, and public administrators responded either with actionable policy changes or sometimes symbolic, "woke" statements that did little to alter the system. In this conceptual paper, we explore the reasons for this via Baudrillard's phases of the image, showing how the word "woke" has moved from roots in the Black community to being weaponized today via its disconnection from this reality, thus trending toward its own hyperreality. In this final phase, the word "woke" has no connection to its former reality, leading to the passage of legislation that upholds White power structures.